2011
DOI: 10.1089/hum.2010.187
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy of Intracranial Glioma Using Interleukin 12–Secreting Human Umbilical Cord Blood–Derived Mesenchymal Stem Cells

Abstract: Clinical trials of gene therapy using a viral delivery system for glioma have been limited. Recently, gene therapy using stem cells as the vehicles for delivery of therapeutic agents has emerged as a new treatment strategy for malignant brain tumors. In this study, we used human umbilical cord blood-derived mesenchymal stem cells (UCB-MSCs) as delivery vehicles with glioma-targeting capabilities, and modified interleukin-12 (IL-12p40N220Q; IL-12M) as a novel therapeutic gene. We also engineered UCB-MSCs to sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(73 citation statements)
references
References 40 publications
0
69
0
2
Order By: Relevance
“…MSCs expressing IL-12 (UCB-MSC-IL12M; Table III) inhibited GL26 intracranial tumor growth and prolonged survival when administered in the contralateral brain hemisphere. 161 The surviving mice were protected from re-challenge with GL26 cells in both contralateral and ipsilateral sides of the brain, indicating a memory response against tumor antigens. 161…”
Section: Immune-stimulatory Gene Therapymentioning
confidence: 93%
“…MSCs expressing IL-12 (UCB-MSC-IL12M; Table III) inhibited GL26 intracranial tumor growth and prolonged survival when administered in the contralateral brain hemisphere. 161 The surviving mice were protected from re-challenge with GL26 cells in both contralateral and ipsilateral sides of the brain, indicating a memory response against tumor antigens. 161…”
Section: Immune-stimulatory Gene Therapymentioning
confidence: 93%
“…Kim et al 41 conducted in vivo efficacy experiments and showed that intratumoral injection of engineered hUCBSC significantly inhibited tumor growth and prolonged the survival of glioma-bearing mice as compared with controls. Ryu et al (2011), 42 recently studied the migratory capacity of hUCBSC mediated by IL-12 toward GL26 mouse glioma cells in vitro and in vivo in gliomas implanted in C57BL/6 mice. Similarly, Park, et al 43 found that overexpression of the SDF-1α receptor CXCR4 in hUCBSC enhanced the migratory capacity toward gliomas.…”
Section: Methodsmentioning
confidence: 99%
“…The underlying principle is that the immunosuppressive cancer location can be changed into one that makes the immune action, not in favour of cancer [167]. Some of the human MSCs have made for the release of IL-12 or IL-18 and they have been experienced in mice having carcinoma of renal cell, cervical tumor and glioblastoma [168][169][170][171][172]. All of these researches to cancer and stem cells inter-related continued company of ILs released by SC along with transfers in immune profile, involving high concentrations of IFNγ, establishment of natural, healthy killer cells and employment of tumor-specific T cells, thus leads to prolonged existence and the estimation of proceeds.…”
Section: Development Of Anticancer Stem Cellsmentioning
confidence: 99%